Effects of Hip Muscle Resistance Training With and Without Feedback on Trunk, Pelvis, and Lower Extremity Motions - Malihe Hadadnezhad; Bahram Sheikhi (Sport Sciences and Health Research)
Introduction: The present study aimed to compare hip muscle resistance training with and without feedback on trunk, pelvis, and lower extremity motions in frontal and sagittal planes among active females with dynamic valgus.Materials and Methods: Twenty-Nine active females (Mean±SD age: 22.8±2.4 years, height: 1.70±0.6 m, weight: 69±7.1 kg) were randomly assigned to a hip muscle resistance training with feedback group (n=15) or a hip muscle resistance training without feedback group (n=14). Both training programs lasted 6 weeks (3 sessions/week). The peak angles of lateral trunk flexion, contralateral pelvic drop, hip ﬂexion, knee ﬂexion, and valgus during single-leg drop landing and single-leg vertical drop jump were assessed in the research participants at baseline and 6 weeks post-training. Unipodal functional screening tests were captured with two standard digital video cameras.Results: After 6 weeks, significant differences were observed in knee valgus and lateral trunk flexion, contralateral pelvic drop, and knee flexion angles, i.e., compared between hip muscle resistance training with feedback and hip muscle resistance training without feedback (P<0.05), except for non-dominant leg hip flexion in single-leg vertical drop jump (P>0.05).Conclusion: In the explored active females with dynamic valgus, hip muscle resistance training with feedback seems to be better at improving trunk, pelvis, and lower extremity motions in frontal and sagittal planes, compared to hip muscle resistance training without feedback; however, no significant difference was observed concerning hip flexion during single-leg vertical drop jump between the study groups.